Therapeutic mammoplasty: a “wise” oncoplastic choice—lessons from the largest single-center cohort from Asia - Koppiker, Chaitanyanand; Joshi, Sneha; Mishra, Rupa; Kelkar, Devaki A.; Chigurupati, Pragnya; Joshi, Anjali; John, Jisha; Kadu, Shweta; Bagdia, Amitkumar; Thakkar, Deepti; Deshmukh, Chetan; Allampati, Harikiran; et al. (Frontiers in Oncology, 2023)
Introduction: A majority of breast cancer patients from India usually present with advanced disease, limiting the scope of breast conservation surgery. Therapeutic mammoplasty (TM), an oncoplastic technique, that permits larger excisions, is quite promising in such a scenario and well suited to breast cancers in medium-large sized breasts with ptosis, and in some cases of large or multifocal/multicentric tumors. Here we describe our TM cohort of 205 (194 malignant, 11 benign) patients from 2012-2019 treated at our single surgeon center in India, the largest Asian dataset for TM Methods: All patients underwent treatment after careful discussions by a multidisciplinary tumor board and patient counselling. We report the clinicopathological profiles, surgical, oncological, cosmetic, and patient-related outcomes with different TM procedures. Results: The median age of breast cancer patients was 49 years; benign disease was 41 years. The breast cancer cohort underwent simple (n=84), complex (n=71) or extreme (n=44) TM surgeries. All resection margins were analysed through intra-operative frozen section assessment with stringent rad-path analysis protocols. The margin positivity rate was found to be 1.4%. A majority of the cohort was observed to have pT1-pT2 tumors and median resection volume was 180cc. Low post-operative complication rates and good-excellent cosmetic scores were observed. The median follow-up was of 39 months. We observed 2.07% local, 5.7% distal recurrences, and disease-specific mortality was 3.1%. At median follow-up, the overall survival was observed to be 95.9% and disease-free survival was found to be 92.2%. The PROMs showed good-to-excellent scores for all types of TMs across BREAST-Q domains. Conclusion: We conclude that in India, a country where women present with large and locally advanced tumours, TM safely expands the indications for breast conservation surgery. Our results show oncological and cosmetic outcomes at acceptable levels. Most importantly, PROMs scores suggest improved overall well-being and better satisfaction with the quality of life. For patients with macromastia, this technique not only addresses the cancer but also improves self-image and reduces associated physical discomfort, often overlooked by women in the Indian setting. Popularization of this procedure will enable Indian patients with breast cancer to receive the benefits of breast conservation.